2020
DOI: 10.3390/cancers12082016
|View full text |Cite
|
Sign up to set email alerts
|

A Bio-Imaging Signature as a Predictor of Clinical Outcomes in Locally Advanced Pancreatic Cancer

Abstract: Purpose: To evaluate the predictive value of 18F-FDG PET/CT semiquantitative parameters of the primary tumour and CA 19-9 levels assessed before treatment in patients with locally advanced pancreatic cancer (LAPC). Methods: Among one-hundred twenty patients with LAPC treated at our institution with initial chemotherapy followed by curative chemoradiotherapy (CRT) from July 2013 to January 2019, a secondary analysis with baseline 18F-FDG PET/CT was conducted in fifty-eight patients. Pre-treatment CA 19-9 level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Fiore et al in their experience, reported that Ca 19.9 levels higher than 698 U/ml were able to identify early progression of pancreatic cancer in patients who had undergone radical resection. In these patients, the odds to develop a recurrence were six times higher (23).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Fiore et al in their experience, reported that Ca 19.9 levels higher than 698 U/ml were able to identify early progression of pancreatic cancer in patients who had undergone radical resection. In these patients, the odds to develop a recurrence were six times higher (23).…”
Section: Discussionmentioning
confidence: 87%
“…However, Ca19.9 assessment has been reported to improve patient selection for neoadjuvant therapies or upfront surgery, followed by adjuvant chemotherapy (22). Furthermore, Ca 19.9 demonstrated its efficacy in combination with PET-CT scan in predicting progression and overall survival in locally advanced PDAC submitted to chemotherapy and radiotherapy (23).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the ability of CA 19.9 to predict the positivity of the lymph node status before surgery, the risk of a resection with positive margins, the need to proceed with a vascular resection, and the analysis of the literature we conducted ( which certainly is not to be considered exhaustive) would seem to confirm the potential of CA 19.9 [ 9 , 17 , 19 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 91%
“…Using ROC curve analysis to assess the cut-offs for all those variables, they found a significant association between pre-surgical CA 19.9 levels, OS, and early recurrence. Notably, they reported a six-time higher risk of early recurrence in the presence of a preoperative level of CA 19.9 > 698 U/mL [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, in this report, CA 19.9 values were also significantly associated with oncological outcomes such as early local recurrence and overall survival. In detail, a CA 19.9 value above 698 U/mL in pre-operatory measurement is associated with a six-times higher risk of early recurrence [ 16 ].…”
mentioning
confidence: 99%